2015
DOI: 10.1024/0301-1526/a000455
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of endovascular revascularisation in patients with acute obstructive mesenteric ischaemia - a single-centre experience

Abstract: Endovascular revascularisation with CDT in combination with AT is feasible, with a technical success rate of 38.5 % (n = 5). Endovascular revascularisation was beneficial for 46.2 % (n = 6) of the patients, who clinically improved following the intervention. The need for secondary explorative laparotomy was rather low, with 38.5 % (n = 5) of the patients. The 30-day-mortality remains high with 30.8 %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Despite the recent therapeutic advances of endovascular techniques for early revascularization, mortality continues to be 30–68% [2] [3] [4]. During intestinal ischemia, the sudden decrease in intestinal blood flow may cause bowel infarction.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the recent therapeutic advances of endovascular techniques for early revascularization, mortality continues to be 30–68% [2] [3] [4]. During intestinal ischemia, the sudden decrease in intestinal blood flow may cause bowel infarction.…”
Section: Introductionmentioning
confidence: 99%
“…Given the low incidence of ATOS, it is challenging for any treatment center to provide feedback on ATOS cases within a relatively short period. There have been a few related studies reporting small sample sizes [ 8 12 , 19 , 20 ]. However, whether or not interventional therapy should be the primary treatment for ATOS is still controversial [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgery for ATOS is associated with a high rate of morbidity and mortality [ 6 , 7 ]. Over the last years, a few studies reported the employment of endovascular revascularization in the treatment of ATOS [ 8 12 ], with rapid blood supply reestablished and relatively small resultant trauma. It was shown by very few studies that endovascular treatment resulted in significantly less bowel resection and shorter bowel syndrome and mortality than open surgery [ 13 ]; however, whether or not endovascular interventional therapy should be the primary treatment for ATOS is still controversial [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, with the advancement of endovascular techniques and devices, transcatheter embolus aspiration with adjunctive thrombolysis and stenting has been used with acceptable results in patients with SMAE, with a reported mortality in these series of 10% to 40% [ 5 , 7 , 11 13 ]. SMAE usually occurs in older patients who have a high incidence of combined medical comorbidities [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The surgery consists of SMA embolectomy, resection of the gangrenous bowel, and a second-look operation if necessary [ 2 ]. Recently, selected endovascular approaches, such as aspiration thrombectomy combined with thrombolysis or stent placement have been reported to have acceptable results with respect to morbidity and mortality [ 4 7 ]. However, the remaining concerns about an endovascular-first approach are the difficulty of identifying bowel infarction by clinical and radiologic evaluation, and reperfusion injury in cases of bowel infarction after endovascular revascularization of the SMA.…”
Section: Introductionmentioning
confidence: 99%